2011
DOI: 10.1016/j.pmrj.2011.07.018
|View full text |Cite
|
Sign up to set email alerts
|

The Pathophysiology of Concussion

Abstract: Concussion is defined as a biomechanically induced brain injury characterized by the absence of gross anatomic lesions. Early and late clinical symptoms, including impairments of memory and attention, headache, and alteration of mental status, are the result of neuronal dysfunction mostly caused by functional rather than structural abnormalities. The mechanical insult initiates a complex cascade of metabolic events leading to perturbation of delicate neuronal homeostatic balances. Starting from neurotoxicity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 93 publications
2
98
0
Order By: Relevance
“…We have now shown that despite intact neuropsychological test performance, the lack of significant post-injury symptoms, and the absence of structural brain damage detected by conventional neuroimaging, differences exist in neural recruitment following mTBI in youth during working memory performance. Overall, these data support the hypothesis of a predominantly functional consequence following mTBI 18,95,96 and provides evidence for neural changes persisting well beyond the acute phase of injury.…”
Section: Single Tasksupporting
confidence: 79%
“…We have now shown that despite intact neuropsychological test performance, the lack of significant post-injury symptoms, and the absence of structural brain damage detected by conventional neuroimaging, differences exist in neural recruitment following mTBI in youth during working memory performance. Overall, these data support the hypothesis of a predominantly functional consequence following mTBI 18,95,96 and provides evidence for neural changes persisting well beyond the acute phase of injury.…”
Section: Single Tasksupporting
confidence: 79%
“…In an effort to restore proper ion balance within the cell, the ATP pump is activated to a greater capacity requiring large amounts of ATP. The imbalance between increased ATP requirements, decreased ATP production and reduced cerebral blood flow quickly leads to an energy crisis within the brain known as spreading depression (Figure 1) [10,14].…”
Section: Pathophysiology Of Concussion and Post-concussion Syndromementioning
confidence: 99%
“…The pathophysiology of mTBI during the acute phase of injury is becoming increasingly well-known suggesting ion imbalance, metabolic disruptions, blood flow abnormalities and autonomic nervous system (ANS) dysfunction as the main culprits [6,[10][11][12][13][14]. When attempting to search for potential mechanisms surrounding PCS; however, findings have been inconsistent and there remains no clear physiologic explanation for this disorder [9,15].…”
Section: Introductionmentioning
confidence: 99%
“…Mild TBI is also an evolving, dynamic injury. [1][2][3][19][20][21] In brief, traumatic forces (e.g., linear, angular, pressure) induce localized physical stress in the brain that instigates a complex series of neurochemical and metabolic changes that may include substantial ionic fluxes, release of excitotoxic levels of neurotransmitters, hypermetabolism leading to energy depletion and hypometabolism, altered cerebral bloodflow and vascular reactivity, edema, and neuroinflammation. Multiple lines of evidence indicate that full return to baseline physiological state can be a prolonged process, requiring weeks or even months, rather than the few days once thought sufficient.…”
Section: Neuropathologymentioning
confidence: 99%
“…[1][2][3][19][20][21][22][23] The direction, speed, and extent of the induced local deformation(s) are critical factors. Primary (immediate) axon transaction (axotomy) is unlikely to occur.…”
Section: Neuropathologymentioning
confidence: 99%